Dampak penerapan IFRS terhadap kualitas laporan keuangan di Indonesia (Studi atas PSAK 50 dan 55 tentang instrumen keuangan) - Destia Dwi Putri (AKT 15 UMY 558, 2015)
*558 This research examined the impact of IFRS on the quality of financial reporting in Indonesia study of SFAS 50 and 55 about financial instruments. The quality of financial statements examined by the variable stock price informativeness, the relevance of the information value of financial derivatives and fair value of financial assets. The quality of financial statements seen by comparing the financial statements with the variables that apply the revised SFAS 50 and 55, revised 2006 with SFAS 50 and 50 revised 2011. The SFAS 50 revised 2006 a pre period and SFAS 50 and 55 revised 2011 is the post period, by comparing The second revision of SFAS, it will be known that implement a revised financial statement which further improve the quality of financial statements, revisions after implementation or prior to the implementation of IFRS. This study uses 27 financial companies listed on the Indonesia Stock Exchange as the sample period 2010-2013. The sampling technique in this study using purposive sampling method. Data were analyzed using multiple linear regression were analyzed using SPSS version 15.0. The results showed that the SFAS 50 and 55 revised 2011 increasing the stock price informativeness and fair value of financial assets in explaining the company's earnings in the future, as well as SFAS 50 and 55 revised 2011 managed to increase the relevance of the information value of financial derivatives. The conclusion from this research is that SFAS has been revised due to the convergence of IFRS in Indonesia may increase accurach accounting information in predicting the performance of the company in the future. Keywords: SFAS 50 and 55 about financial instruments, stock price informativeness, value relevance of financial derivatives and fair value of financial assets.